RURAL INDUSTRIALISATION AS A CONCEPT SEGMENT OF THE INTEGRAL RURAL DEVELOPMENT IN REPUBLIC OF SRPSKAPOTENTIALS AND PERSPECTIVES - Popović, Goran (Economics of Agriculture, 2006)
The process of the general reforms in Bosnia and Herzegovina society, whose equal entity is also Republic of Srpska, is in a swing. Their aim is in the first place, structure coordination of the social economic and political system with the EU standards. The processes from the rural economy sphere and the application of the integral rural development concept are not enough developed . Republic of Srpska will still for a long time belong to a rural European region, particularly after entering the Union. That is why the economic, the social and the demographic problems at the rural territories are to be solved rapid and with a plan. The available the natural resources point out to the reserves in a development of the unagricultural, above all, of the industrial sector